2018
DOI: 10.3390/safety4040059
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Predictive Power for Traffic Accident Involvement; Celeration Behaviour versus Age, Sex, Ethnic Origin, and Experience

Abstract: Driver celeration behaviour theory (DCBT) assumes that risk for a driver of causing a road crash is linearly related to speed change in any given moment and that the speed change variable (celeration) captures all risk (all vehicle control movements can be measured as acceleration). When sampling driver behaviour, the celeration variable is calculated as the average of all absolute values of acceleration when the vehicle is moving. DCBT predicts that no other variable can be a stronger predictor of (the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The correlation coefficient ranges from -0.18 to -0.12 (p<0.05). The results of the research presented in work [1] confirm the weak correlation between the driver's experience and the values of acceleration. The correlation studies presented in [1,16,39] show that the experience of a city bus driver does not significantly influence the number of traffic violations, accidents and dangerous situations on the road.…”
Section: Discussionsupporting
confidence: 53%
“…The correlation coefficient ranges from -0.18 to -0.12 (p<0.05). The results of the research presented in work [1] confirm the weak correlation between the driver's experience and the values of acceleration. The correlation studies presented in [1,16,39] show that the experience of a city bus driver does not significantly influence the number of traffic violations, accidents and dangerous situations on the road.…”
Section: Discussionsupporting
confidence: 53%
“…From the review of literature, it was found that among the data collection method used in the published articles were surveys, analysis of traffic accident or police report data, and using virtual reality experiments. Af Wåhlberg (2018), Matthews and Norris (2002), Bener et al (2013), Factor et al (2012), Papacostas and Synodinos (1988), Patil et al (2006), andPutranto andAlyandi (2019) carried out surveys to understand driving behavior. This is called the Driver Behaviour Questionnaire (DBQ) that consists of lapses, mistakes, and slips.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Driving behavior studies of occupational drivers were also conducted to assess the drivers' behavior (Af Wåhlberg, 2018;Dorothy et al, 1998;Kurniasih, 2019). Another interesting topic of driving behavior is the perception of drivers to police bias while stopping them whereas minor ethnicities (i.e.…”
Section: Socio-demographics Backgroundmentioning
confidence: 99%